Small extracellular vesicles from mesenchymal stem cells: A potential Weapon for chronic non-healing wound treatment - Wei, Qian; Liu, Xi; Su, Jian-Long; Wang, Ya-Xi; Chu, Zi-Qiang; Ma, Kui; Huang, Qi-Lin; Li, Hai-Hong; Fu, Xiao-Bing; Zhang, Cui-Ping (Frontiers in Bioengineering and Biotechnology, 2023)
Chronic non-healing wounds have posed a severe threat to patients mentally and physically. Behavior dysregulation of remaining cells at wound sites is recognized as the chief culprit to destroy healing process and hinders wound healing. Therefore, regulating and restoring normal cellular behavior is the core of chronic non-healing wound treatment. In recent years, the therapy with mesenchymal stem cells (MSCs) has become a promising option for chronic wound healing and the efficacy has increasingly been attributed to their exocrine functions. Small extracellular vesicles derived from MSCs (MSC-sEVs) are reported to benefit almost all stages of wound healing by regulating the cellular behavior to participate in the process of inflammatory response, angiogenesis, re-epithelization, and scarless healing. Here, we describe the characteristics of MSC-sEVs and discuss their therapeutic potential in chronic wound treatment. Additionally, we also provide an overview of the application avenues of MSC-sEVs in wound treatment. Finally, we summarize strategies for large-scale production and engineering of MSC-sEVs. This review may possibly provide meaningful guidance for chronic wound treatment with MSC-sEVs.